Africa's Moment - Wolfensohn, James D. (2017)
This is a speech given by Mr. Wolfensohn to the United Nations Economic Commission for Africa, on January 27, 1998 at Addis Ababa. He presented a development agenda in Africa which covers: human resource development, capacity building, rural development and rural transformation, private sector development, infrastructure, conflict prevention and resolution, public sector reform and good governance, and gender and environment. To achieve all these, it is important to establish partnerships with the governments of the developing countries, donor community, private sector, and nongovernmental organizations and civil society. He also addressed the importance of relieving African debt.